2007
DOI: 10.1089/dis.2007.104706
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Health Information Technology to Improve the Process of Health Care Delivery: A Case Study

Abstract: Integration of health information is critical to the provision of effective, quality care in today's fragmented health care system. The increasing prevalence of chronic conditions and the demand for a comprehensive understanding of patient health on the part of providers are driving the need for the integration of health information through electronic health information systems. Two distinct health information systems currently utilized in the health care field include electronic medical records (EMR) and chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Earlier studies on PHRs demonstrated their usefulness in improving the quality of care for patients with chronic illnesses [37], in controlling costs [3], and in reducing health care disparities [38-40]. The accelerated efforts from ICT and health care companies and their partnerships will likely substantially increase the availability and usability of PHRs.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies on PHRs demonstrated their usefulness in improving the quality of care for patients with chronic illnesses [37], in controlling costs [3], and in reducing health care disparities [38-40]. The accelerated efforts from ICT and health care companies and their partnerships will likely substantially increase the availability and usability of PHRs.…”
Section: Discussionmentioning
confidence: 99%
“…The challenges are not insignificant and at a minimum include being able to articulate the value of PHRs for individuals along the full wellness/sickness spectrum. The value and/or utility of PHRs outside of transaction-based functions (eg, appointment scheduling and medication refills), such as the potential benefits of PHRs for those managing chronic conditions [24], have not been sufficiently researched. However, as we work to increase our understanding of the uses and utility of PHRs, it would also serve the interests of public health to focus on issues related to data liquidity [25], personal health tools and platforms [5], general health literacy and education [26], and the ways in which these approaches and systems work to improve health outcomes and the quality of care as well as influence and streamline public health practice.…”
Section: Public Health’s Rolementioning
confidence: 99%
“…Other studies show that both EMR and electronic health records can significantly reduce the costs of health care, increase the quality of health care services, and eventually improve the community's health status (9). Therefore, due to the importance of EMR, some programs have been developed for its adoption and use in health care industries.…”
Section: Introductionmentioning
confidence: 99%